Fingerprint Analysis in Digital Forensics: A Bibliometric Examination - Kosasih, Jaylu; Rosnawati, Emy; Nurhayati (Proceedings of The ICECRS, 2023)
This bibliometric analysis, conducted on December 24, 2022, aims to unravel the research landscape surrounding "fingerprints" in the realm of digital forensics. Employing the VOSviewer application and Lens.org data, we gathered 134 journal articles from 2012 to 2022, focusing on the field of law. Notably, 2019 emerged as a pivotal year with 35 journal articles, while the United Kingdom, United States, and Switzerland led in publication output. K.J.R. Liu exhibited the highest productivity with 15 journal articles, and the University of Nottingham proved to be the most prolific institution. The Journal of Business Ethics stood out as the most influential publication. Our topic analysis revealed a single cluster, with "human" being the most prevalent term. This research underscores the significance of fingerprints in individual identification, be it through smartphone or laptop sensors or DNA analysis for ancestral tracing, offering valuable insights for the global scientific community. Highlights: Comprehensive Data Analysis: Our study analyzes 134 journal articles from 2012 to 2022, providing a comprehensive overview of research trends in digital forensics related to fingerprints. Productivity Insights: K.J.R. Liu's prolific output of 15 journal articles and the University of Nottingham's leading role in publication output shed light on key contributors in this field. Fingerprint Significance: The research underscores the critical role of fingerprints in individual identification, whether through digital sensors or DNA analysis, with implications for broader forensic applications. Keywords: Digital Forensics, Fingerprint Analysis, Bibliometric Research, Individual Identification,Research Patterns